Marketing priority analysis based on marketing mix in Luvrina Fashion - Ragil Pardiyono; Rina Indrayani (STIE Binaniaga, 2019)
Luvrina Fashion is a specialty clothing store located in the mature woman Jatinangor Town Square. Fashion Luvrina sales value in recent months has decreased. As the Micro, Small, Medium, he needs a business management that consists of financial management, marketing, production, distribution, and human resources to conduct its business. Marketing aspect is an important factor for companies to carry out his life (Bayu Promukoto, 2018). Thus the purpose of this research is the analysis of marketing priorities based model of the marketing mix. Tools of data collection using a questionnaire with 23 variables and the respondents as many as 100 visitors. The method used is the analysis of factors with steps Preparing Raw Data Matrix, Matrix Correlation between Variables, Calculations Eigenvalue, Extraction of factors, weighting factors, Rotation Factor, and determination of manifest variables that Form Factor. The results of data processingdikesimpulkan that marketing priorities with marketing mix models in a fashion luvrina is factor 1 has eigenvalue equal to 17.950 which includes the availability of diverse models of clothes, clothing quality, low price, method of payment by debit card, as well as their discount. The next priority is a factor 2, factor 3, a factor of 4, and a factor of 5. Keywords: Marketing, Marketing Mix, Factor Analysis